Interpretation of the Term "Reindustrialization" in the Conditions of Globalization - Maltsev, Andrei Alexandrovich; Mercier-Suissa, Catherine; Mordvinova, Arina Eduardovna (Economy of Regions, 2017)
The authors state the hypothesis that the reindustrialisation tends to be globally understood as having different features for every country. The industrial policy of each state to reindustrialize the national economy determines these special features. The methodology of the research is presented by the wide range of different tools and methods. It includes the systematic approach to the interpretation of reindustrialisation, structuring the existing interpretations of reindustrialisation, criteria-based analysis of broader concepts, historical analysis of statistic data. Furthermore, we used basic scientific methods of analytical summary, quantitative analysis, deduction and abstraction. To prove the suggested hypothesis, the authors have compared key trends in the global economy with the existing theoretical approaches to reindustrialization in national and foreign economic research. We have analyzed the interpretation of reindustrialization as a global economic trend and as a specific state policy. The main features of reindustrialization process and its difference from reshoring- are examined. We have classified the key interpretations of “new industrialization” and “reindustrialization” terms tacking into account their correlation. To identify the common and specific features of the new industrialization and reindustrialization processes, the author used the criteria-based analysis. This allowed us to determine the most important qualitative and quantitative features of reindustrialization as a global tendency. Furthermore, we have classified the basic tools of state reindustrialization policy in number of developed and developing countries.